Integrating Real-Time Facial Ethnicity Classification with a Godot Game Client for Personalized Cultural Interactive Exhibition - Trisna Gelar; Muhammad Rizqi Sholahuddin; Aprianti Nanda Sari; Ais Laksana; Satryo Haryo; Rafli Fadhilah; Gianluigi Julian; Daffa Muzhaffar (Politeknik Negeri Cilacap, 2026)
Addressing the recognized limitation of non-adaptive